2013
DOI: 10.5301/jbm.5000043
|View full text |Cite
|
Sign up to set email alerts
|

K-RAS Mutation Profile in Puerto Rican Patients with Colorectal Cancer: Trends from April 2009 to January 2011

Abstract: The frequency of K-RAS mutations ranges between 30% and 48% among the Caucasian, Asian, and European populations and these mutations are predictors of response to EGFR therapies. We sought to determine the expression of K-RAS gene mutations among colorectal cancer patients in PuertoRico. A retrospective study was conducted to determine the expression of mutant K-RAS among colorectal cancer patients in Puerto Rico between April 2009 and January 2011. The mutant expression of K-RAS was found in 39% (n=195) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
2
3
1
Order By: Relevance
“…In a much smaller sample of 46 patients, we found that males are more likely to have mutant KRAS status than females [37]. Association between mutations and male gender was also reported in the Puerto Rican patient population [38].…”
Section: Kras Mutation and Correlation With Clinicopathologic Charactsupporting
confidence: 71%
See 1 more Smart Citation
“…In a much smaller sample of 46 patients, we found that males are more likely to have mutant KRAS status than females [37]. Association between mutations and male gender was also reported in the Puerto Rican patient population [38].…”
Section: Kras Mutation and Correlation With Clinicopathologic Charactsupporting
confidence: 71%
“…For example KRAS mutations correlated with regional lymph node metastasis and tumor stages in 88 patients from Sweden and 99 patients from Japan [49]. In a study of 501 Puerto Rican patients, mutation were detected more frequently in patients with distant metastases compared to those without (50% vs. 37.4%; P=0.020) [38]. Another series of 254 Japanese patients also reported a significant association between poor RFS and MT KRAS [50].…”
Section: Correlation Between Kras Mutation Status and Prognosismentioning
confidence: 96%
“…We also compared the mutational frequencies of actionable genes for CRC and reported significant differences for PRH in KRAS/NRAS , BRAF , and ERBB2 amplification. The high mutational frequency of KRAS reported for PRH differs from a previous study with PRH that found KRAS mutations in 39% of CRC tumors 40 . However, a similar KRAS mutational frequency was reported for USH (59%), 41 while a higher frequency was reported for Mexicans (86%) 42 .…”
Section: Discussioncontrasting
confidence: 60%
“…Overall, KRAS mutation frequencies in our PRH cohort (31.9%) are lower than those reported in other racial/ethnic groups, including non-Hispanic Blacks (59%) and non-Hispanic Whites (37–41%) [ 33 , 34 , 35 , 41 ]. A previous study in a separate cohort of 501 PRH reported a slightly higher but comparable prevalence of KRAS mutations (39%) [ 42 ]. The percentage of tumors with MSI in our cohort was markedly lower (4.3%) than what has been reported in African Americans (14–19%) and non-Hispanic Whites (9–13%) [ 33 , 37 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 94%